Improvement of the photostability of cycloalkylamine-7-sulfonyl-2, 1, 3-benzoxadiazole-based fluorescent dyes by replacing the dimethylamino substituent with cyclic amino rings. (22nd March 2022) - Mehta, Pramod Kumar; Ryu, Ki; Kim, Chan Kyung; Lee, Keun-Hyeung
Abstract : Replacing the dimethylamino substituent of a fluorescent probe with 3- and 4-membered cyclic amine rings led to significantly enhanced photostability. Abstract : The development of visible light excitable fluorophores that exhibit long wavelength emission has drawn significant attention due to recent extensive applications of fluorescence imaging techniques. N, N -Dimethylamine-7-sulfonyl-2, 1, 3-benzoxadiazole (ABD) with visible light excitation exhibits red emission at around 580 nm in aqueous solutions. We designed several ABD analogs that had different sizes of cyclic amine and synthesized ABD analog-labelled amino acids (1–5 ). The fluorescently labelled amino acids (1–5 ) were facilely synthesized using solid phase synthesis with high yields (>65%). 1–5 dissolved well in aqueous solution, MeOH, DMF, THF, and CH2 Cl2 . The photophysical properties (molar extension coefficient, Stokes shift, quantum yield, and fluorescence lifetime and so on) and photostability of 1–5 were investigated in these solvent systems. 1–5 showed higher brightness in an aprotic solvent than a protic solvent and the quantum yield of 1–5 showed high dependence on the solvent polarity. Lippert–Mataga plots suggested the dependence of the polarizability of the excited state of 1–5 on the aprotic/protic nature of the solvents. Replacing the dimethylamino substituent of the fluorescent probe with 3- and 4-membered cyclic amine rings led to significantly enhanced photostability. 3-Membered aziridine ring substitution induced significantly improved photostability under visible light as well as UV irradiation and resulted in enhanced brightness and an increase of the fluorescence lifetime.